Simulation of Void Detection System using Gamma-Ray Compton Scattering Technique - Mona Berlian Sari; Rahadi Wirawan; Abdul Waris; Hong Joo Kim; Mitra Djamal (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
A simple void detection system for concrete was successfully developed using high-penetration gamma rays with Compton scattering. This research attempted to identify a void in the subsurface of a concrete volume that could not be accessed from any of the sides. Monte Carlo simulation using GEANT4 toolkit was performed to investigate the gamma-ray backscattering events. An NaI(Tl) detector was used with 60Co and 137Cs as gamma-ray sources. The void's location was successfully detected during material target scanning. Density discrepancies conduce variance of the backscattering peak produced due to the presence of a void. Compared to 60Co as the gamma-ray source, 137Cs is a better choice for application in NDT systems using Compton scattering.